Abstracts of the Scandinavian Workshop on Applied Eye Tracking (SWAET 2018) - Daniel Barratt; Raymond Bertram; Marcus Nyström (Bern Open Publishing, 2018)
This document contains the abstracts for the 2018 Scandinavian Workshop on Applied Eye Tracking (SWAET 2018) which was held at Copenhagen Business School, Denmark, 23 to 24 August, 2018..